Assessment of bismuth film gold ultramicroelectrode array for the determination of trace heavy metals in water - Bahinting, Sandra Enn D.
This study reports the coupling of bismuth film electrodes (BFEs) with ultramicroelectrode array (UMEA) for the simultaneous determination of the trace level Cd (II) and Pb (II) by square wave anodic stripping voltammetry (SWASV). The BFEs is prepared using in-situ plating by simultaneously depositing the bismuth film and metals cations at -1.2 deposition potential in gold ultramicroelectrode array substance. In order to benefit from the advantages of BFEs and UMEA, the effects of several experimental and instrumental conditions such as concentration of Bi (3+) ions and supporting electrolyte, pre-concentration time, and SWASV parameters (frequency, amplitude and step potential), were optimized. The Box Behnken Design was used to further evaluate the interaction of the SWASV parameters to which higher sensitivity is achieved by high amplitude at low frequency and step potential. Moreover, interferences due to the presence of other metal cations, salts and organic compounds were investigated. The presence of Cu (II) ions has profoundly affected the current peak area of both metals present. Using the selected conditions, calibration graph in the range of 10-100 μg/L for both metals were established with reproducibility for 8 consecutive runs were of % RSD of 10.14 for Cd and % RSD of 11.18 for Pb. Finally, the limit of detection for both metals was down to 7μg/L and 5μg/L for Cd (II) and Pb (II) ions.